Polycythemia Secondary to Pheochromocytoma - Raheel Raza, Saima Ambreen, Hassan Mumtaz, Shahzaib Ahmad, Hadin Darain Khan (Journal of Rawalpindi Medical College, 2021)
Polycythemia, also known as polyglobulia, is a clinical condition characterized by an increased number of red blood cells (RBC) or haematocrit concentrations in the peripheral blood. It can either be primary (polycythemia vera) or secondary, which can be congenital or acquired; the most common causes include obstructive sleep apnoea, obesity, hypoventilation, Pickwickian syndrome, Chronic obstructive pulmonary disease (COPD), and lastly, pheochromocytoma. Here we present a case of a 54-year-old male with a four-day history of altered state of consciousness (ASOC), right-sided body weakness, and respiratory difficulty. After a thorough history, examination, and investigation, he was diagnosed as a case of polycythemia secondary to pheochromocytoma. Early diagnosis and intervention are critical to save the patient’s life.